ChemInform Abstract: A Facile Synthesis of New Coumarin‐3, 4‐dihydropyrimidin‐2(1H)‐ones/thiones Dyads. Issue 37 (September 2015) - Benazzouz, Amina; Makhloufi‐Chebli, Malika; Khatir‐Hamdi, Nejla; Boutemeur‐Khedis, Baya; Silva, Artur M. S.; Hamdi, Maamar
Abstract The title compounds are prepared by three—component Biginelli reaction of coumarins, aldehydes, and (thio)urea.